2002
DOI: 10.1046/j.1471-4159.2002.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Identity of adenylyl cyclase isoform determines the G protein mediating chronic opioid‐induced adenylyl cyclase supersensitivity

Abstract: To determine the intracellular signal transduction pathway responsible for the development of tolerance/dependence, the ability of G z a to substitute for pertussis toxin (PTX)-sensitive G proteins in mediating adenylyl cyclase (AC) supersensitivity was examined in the presence of defined AC isoforms. In transiently l-opioid receptor (OR) transfected COS-7 cells (endogenous inhibitory G proteins: G i a2, G i a3 and G z a), neither acute (1 lmol/L) nor chronic morphine treatment (1 lmol/L; 18 h) influenced intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In addition, G␤␥ could activate specific isozymes of adenylyl cyclase in the presence of Gs ␣-subunit, such as type II (Weitmann et al, 2001) and IV (Debernardi et al, 1993). AC superactivation has been shown to be isozymespecific, with the ability of long-term opioid treatment to superactivate the AC type I, V, VI, and VIII but not the type II, III, IV, and VII (Avidor-Reiss et al, 1996Ammer and Christ, 2002). In N 2 A cells, the expression of type II, III, IV, VI, and VII adenylyl cyclase is detected by RT-PCR (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, G␤␥ could activate specific isozymes of adenylyl cyclase in the presence of Gs ␣-subunit, such as type II (Weitmann et al, 2001) and IV (Debernardi et al, 1993). AC superactivation has been shown to be isozymespecific, with the ability of long-term opioid treatment to superactivate the AC type I, V, VI, and VIII but not the type II, III, IV, and VII (Avidor-Reiss et al, 1996Ammer and Christ, 2002). In N 2 A cells, the expression of type II, III, IV, VI, and VII adenylyl cyclase is detected by RT-PCR (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This relatively poor ability of G␣o to mediate supersensitization may relate to the expression level of G␣o, the weak ability of G␣o to couple to adenylyl cyclase (McKenzie and Milligan, 1990;Moon et al, 2001;Clark et al, 2003), or the fact that G␣o is not endogenous to C6 cells (Charpentier et al, 1993), and so the correct machinery is not in place, including isoforms of adenylyl cyclase. This last point is particularly pertinent because Ammer and Christ (2002) have shown that the ability of G␣ subunits to mediate adenylyl cyclase supersensitivity is isoform-specific. There was a much higher level of supersensitization in C6 cells expressing G␣o-RGS/PTXi, indicating that endogenous RGS proteins reduce the magnitude of supersensitization.…”
Section: G␣o and Rgs Proteins In Adenylyl Cyclase Supersensitization 219mentioning
confidence: 99%
“…The authors suggest that simultaneous activation of multiple G␣ proteins may be necessary (Tso and Wong, 2001), although a role for G␣o was not investigated. In COS-7 cells that express G␣z, G␣i 2 , and G␣i 3 , but not G␣o, Ammer and Christ (2002) have shown that supersensitization is observed but suggested that the ability of different G␣ subunits to induce supersensitization is dependent on the type of adenylyl cyclase expressed. Additional factors controlling adenylyl cyclase activity, including levels of adenylyl cyclase-stimulating agents such as Ca 2ϩ /calmodulin, or levels or phosphorylation state of certain adenylyl cyclase isoforms, as well as changes in levels and phosphorylation state of cAMP response element-binding protein have all been implicated in the development of adenylyl cyclase supersensitization (for review, see Law et al, 2000).…”
mentioning
confidence: 99%
“…We have previously shown that animals undergoing restraint stress were immunologically vulnerable if they were morphine-tolerant (Bayer et al, 1994;Mellon et al, 2001). Neuroadaptation that occurs during chronic opioid administration is thought to involve changes in levels of neurotransmitters such as norepinephrine and GABA (Jolas et al, 2000;Van Bockstaele et al, 2001), various receptors systems such as orphanin FQ, cholecystokinin, and aminopeptidases Laorden et al, 1997;Milanes et al, 1997;Yuan et al, 1999;Brundege and Williams, 2002;Irazusta et al, 2003), and expression of major second messenger signaling factors such as protein kinase C, adenylate cyclase, G protein-coupled receptors, and cAMP response element-binding protein (Parolaro et al, 1993;Lane-Ladd et al, 1997;Bernstein and Welch, 1998;Shen et al, 2000;Tso et al, 2000;Ma et al, 2001;Shichinohe et al, 2001;Ammer and Christ, 2002;Irazusta et al, 2003). It has been theorized that these central neuroadaptations may mediate sensitized responses to stressors and that relapse to drug-taking behavior may be due to this stress vulnerability (Self and Nestler, 1998;Houshyar et al, 2001a;Mutasa, 2001;Sarnyai et al, 2001;Weiss et al, 2001).…”
Section: Antagonism Of Nmda Receptors 797mentioning
confidence: 99%